Green office practices towards sustainable work environments / Norafiza Mohd Hardi, Nurliyana Abas and Azlyantiny Mohammad - Mohd Hardi, Norafiza; Abas, Nurliyana; Mohammad, Azlyantiny (Universiti Teknologi MARA, Kedah, 2024)
A Green Office is a workplace that prioritizes sustainability, environmental responsibility, and efficiency in its operations and practices. The concept is to reduce the environmental impact of office operations and promote a healthier and more environmentally friendly workplace. According to the World Wide Fund for Nature Finland (2016), green office is an environmental management system for offices and an ideal tool for successful and sustainable organizations. Organizations that practice a green workplace can easily reduce their ecological footprint, promote sustainable lifestyles and mitigate climate change. Yee Sin et al. (2021) stated that Green Office refers to environmentally responsible office practices and resource efficiency that help reduce the environmental impact of office activities and contribute to sustainable development. The US Environmental Agency defined a green office as an environmentally responsible structure with limited use of available resources. Malaysia has been actively working on sustainable development and green initiatives, including plans for green technology. According to Ministry of Energy, Green Technology and Water (2017), the Green Technology Master Plan (GTMP) 2017-2030 has earmarked green growth as one of six priorities altering the trajectory of the nation’s growth. The GTMP creates a framework that facilitates the mainstreaming of green technology into Malaysia's planned developments. It also encompasses the four pillars set in the National Green Technology Policy (NGTP): energy, environment, economy, and social.